Introduction to the special issue “Higher education during and after COVID in Central and Eastern Europe” - Dunajeva, Jekatyerina (Przegląd Krytyczny, 2022)
Is there a need for more research on the effects of COVID-19 on education? While there is research suggesting that the impacts and “the troubling effects of the pandemic on research and higher education… might be felt for years to come” (The Lancet Editorial, 2020), there is also discernible pandemic fatigue, not only among the population, but researchers and subjects of research as well (Patel, Webster, Greenberg, Weston, & Brooks, 2020). Indeed, there has been an overabundance of published research articles in nearly all disciplines about the pandemic. The purpose of the current special issue is not to repetitively take stock of what happened during the pandemic but rather explore how the pandemic transformed the education system while rethinking certain practices and strategies engrained in the education system. To some extent, then, taking stock of what we know about the pandemic should help us prepare for the era some call the “new normal post-COVID-19 era” (Cahapay, 2020).